2019
DOI: 10.1021/acs.joc.9b02262
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Sensors Based on Fluorescence Quenching of the 2-AminobenzimidazoleFluorophore

Abstract: The fluorescence emission of the parent 2-aminobenzimidazole (ABZ, 1), the mono- and disubstituted derivatives (2, 3), 2-aminonaphthoimidazole (4), and 4-amino dinaphthodiazepine 5 (λem = 315–400 nm) is strongly quenched in the presence of aqueous hydrogen peroxide. The quenching process is dual: for diazepine 5, quenching is dynamic at lower H2O2 concentrations with linear reduction of the fluorescence lifetime from 4.3 to 2.6 ns. At higher H2O2 concentrations, a second species appears in the absorption and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…[6] 2-Aminobenzimida-zole was also utilized as a ligand to modify the structures of zeolitic imidazolate frameworks (ZIFs), thereby adjusting the properties of the corresponding materials. [7] Besides, the 2-aminobenzimidazole skeleton is prevailing in chemical sensors for the detection of anions [8] as well as in corrosion inhibitors. [9] In view of the widespread applications, expedient synthetic approaches were described for accessing 2aminobenzimidazoles.…”
Section: Introductionmentioning
confidence: 99%
“…[6] 2-Aminobenzimida-zole was also utilized as a ligand to modify the structures of zeolitic imidazolate frameworks (ZIFs), thereby adjusting the properties of the corresponding materials. [7] Besides, the 2-aminobenzimidazole skeleton is prevailing in chemical sensors for the detection of anions [8] as well as in corrosion inhibitors. [9] In view of the widespread applications, expedient synthetic approaches were described for accessing 2aminobenzimidazoles.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in medicinal chemistry have demonstrated them as potential drug motifs for the pharmaceutical industry [ 7 ]. They have also well-known applications in chemo-sensing [ 8 ], fluorescence [ 9 ], crystal engineering [ 10 ], corrosion science [ 11a,b ] and asymmetric catalysis [ 12 ]. The bioactivity of drug molecule depends predominantly on their interaction with drug targets, such as proteins, enzymes, nucleic acids and the biological membranes [ 13a,b ].…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that totally switched-off fluorescence emission was observed with the higher Cu 2+ ions concentrations of 100 ppm of Cu 2+ ions solution. To explain the fluorescence (static or dynamic) turn off/quenching in the case of SNC-DETA-EA, we employed the Stern–Volmer equation as presentedhere. , with I 0 and I being the intensities observed, respectively, in the absence and presence of quencher, and Q is quencher concentration, K sv is the Stern–Volmer constant, and n is the binding constant.…”
Section: Resultsmentioning
confidence: 99%